Peace psychology - Christie, Daniel J.; Noor, Noraini M. (Oxford University Press, 2013)
Since the inception of modern psychology, psychologists have distinguished between thoughts and actions. Similarly, peace psychologists distinguish sharply between conflicts and violence which they equate with thoughts and actions, respectively. Conflict (between individuals or groups) is often defined as the perception of incompatible goals, whether real or imagined, while violence refers to coercive actions that are intentionally carried out with the intent of harming others. Therefore, in peace psychology the sources and consequences of conflict are often treated separately from violence. In addition, peace psychologists distinguish two general types of violence: episodic and structural. An episode of violence is a discrete, observable event which is aimed at inflicting physical harm on an individual or group. The episode may occur once or repeatedly. While episodes may be dramatic and deadly, structural violence is insidious and normalized in societies; structural violence is “just the way things are.” Structural violence kills people just as surely as violent episodes but structural violence kills slowly and curtails life spans through the deprivation of human rights and basic human needs. For example, if there is enough food in the world for everyone, yet some people die of starvation, then structural violence is taking place. Structural violence is supported and justified by the dominant narratives of a society or, put another way, structural violence is supported by cultural violence, the latter of which refers to the symbolic sphere of human existence. In regard to peace, negative peace interventions are designed to prevent and mitigate violent episodes while positive peace interventions are aimed at the reduction of structural violence. To elaborate: negative peace interventions can be tailored to various phases of a violent episode: (1) conflict phase which precedes the violent episode, (2) violent episode phase, or (3) post violence phase. In contrast, structural and cultural violence cannot be prevented because all societies have some degree of ongoing structural and cultural violence. Positive peace interventions involve social and cultural transformations that reduce structural and cultural violence and promote a more equitable social order that meets the basic needs and rights of all people. Peace psychology therefore deals with the patterns of thoughts, feelings, and actions of individuals and groups that are involved in violent episodes as well as the prevention and mitigation of violent episodes. Peace psychology also deals with thoughts, feelings, and actions that (re)produce social injustices as well as socially just arrangements between individuals and groups. Sustainable peace requires continuing efforts to craft facilitative synergies between nonviolent means and social just ends, that is, the pursuit of negative and positive peace.